Effectiveness of Office Asset and Logistics Management Innovation in Improving Government Operational Efficiency in the Household Section of the General Bureau of the Regional Secretary of East Java Province - Vicky Rahmawan Putra; Fedianty Augustinah; Eny Haryati (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This research seeks to evaluate how asset and logistics management innovation enhances operational efficiency in the Household Division of the East Java Provincial Secretariat. The study focuses on the bureaucratic reform initiative aimed at attaining transparent, accountable, and effective asset management via digital transformation. The emphasis lies on how digital inventory systems, purchasing methods, and asset allocation aid in minimizing budget waste and improving efficiency. This research utilized a qualitative descriptive strategy through a case study technique. Data were gathered via extensive interviews, direct observation, and analysis of internal documents, subsequently undergoing data reduction and triangulation to confirm validity. The results indicate that the adoption of the e-inventory system has enhanced administrative efficiency by as much as 30%, but issues persist with data integration and employee digital skills. Additionally, the lack of a real-time public monitoring system restricts transparency in logistics management. The research advises enhancing employee training, creating cohesive SOPs, and adopting technology-driven assessment systems. These actions are anticipated to promote effective, efficient, and sustainable asset management in the East Java Provincial Secretariat.